Ketersediaan dan Kebutuhan RTH Publik sebagai Infrastruktur Evakuasi Bencana di Kawasan Perkotaan: Studi Kasus Kecamatan Palu Timur, Kota Palu - Basri, Iwan Setiawan; Arifin, Rosmiaty; Sarifuddin; Pelealu, Regina Excelsia (Prodi PWK Universitas Tadulako, 2025)
The demand for space in urban areas is significant due to population and economic growth. As a result, the need for space has increased sharply. The most obvious impact is the expansion of the existence of Green Open Space (GOS). This study aims to assess the availability of public GOS in East Palu District by examining its proportion relative to the total land area and population, its potential role in disaster evacuation, and the identification of land suitable for future development. A descriptive quantitative method is employed, referencing national regulations such as Law No. 26 of 2007 and Ministry of Public Works Regulation No. 5 of 2008. Geographic Information Systems (GIS) were used for land mapping analysis. The findings indicate that in 2023, East Palu has 44.11 hectares of public GOS. With the district covering 970 hectares, the ideal allocation for green spaces is 149.9 hectares (20%). Given a population of 44,491, the required GOS amounts to 889.82 hectares, revealing a significant shortfall of 845.71 hectares. Furthermore, the identification of only 44.85 hectares of land as suitable for further GOS development remains insufficient. GOS is essential not only for aesthetics and recreation but also as crucial infrastructure for enhancing urban resilience during disasters. It is therefore vital for agencies involved in land management, urban planning, and disaster response to collaborate, ensuring that public GOS is prioritized in sustainable city planning.